2001
DOI: 10.1093/carcin/22.6.851
|View full text |Cite
|
Sign up to set email alerts
|

p53 protein at the hub of cellular DNA damage response pathways through sequence-specific and non-sequence-specific DNA binding

Abstract: Our environment contains physical, chemical and pathological agents that challenge the integrity of our DNA. In addition to DNA repair, higher multicellular organisms have evolved multiple pathways of response to damage including programmed cell death-apoptosis. The p53 protein appears to sense multiple types of DNA damage and coordinate with multiple options for cellular response. The p53 protein activities depend upon its DNA binding. Specific p53 protein post-translational modifications are required for eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
112
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(114 citation statements)
references
References 113 publications
1
112
0
1
Order By: Relevance
“…The ATP-dependent chromatin remodeler CSB has been shown to interact with the tumor suppressor p53, and both proteins play important roles in a variety of overlapping nuclear processes (8,11,15,22,36). In this study, we have found that the association of CSB and p53 with chromatin is reciprocally regulated, and we have provided mechanistic insights into this regulation and how these two proteins may coordinate their activities.…”
Section: Discussionmentioning
confidence: 68%
“…The ATP-dependent chromatin remodeler CSB has been shown to interact with the tumor suppressor p53, and both proteins play important roles in a variety of overlapping nuclear processes (8,11,15,22,36). In this study, we have found that the association of CSB and p53 with chromatin is reciprocally regulated, and we have provided mechanistic insights into this regulation and how these two proteins may coordinate their activities.…”
Section: Discussionmentioning
confidence: 68%
“…The consequence of hormone exposure is the induction of persistent differences in molecular pathways between the epithelial cells in the hormone-treated and mature mammary gland that dictate the proliferative responses upon a carcinogenic insult. Additional data to support this hypothesis have been published recently (19)(20)(21).The tumor suppressor protein p53 protein, which is situated in the hub of cellular DNA damage pathways in higher organisms, is central to the cellular response to a variety of potentially damaging extracellular stimuli including UV light, ␥-irradiation, chemical carcinogens, and chemotherapeutic agents (22,23). Depending on the insult it can evoke cell cycle arrest (24-28), DNA repair (29), or apoptosis (30, 31) through sequence-specific and nonsequence-specific DNA binding and through both positive and negative mechanisms (32).…”
mentioning
confidence: 92%
“…The tumor suppressor protein p53 protein, which is situated in the hub of cellular DNA damage pathways in higher organisms, is central to the cellular response to a variety of potentially damaging extracellular stimuli including UV light, ␥-irradiation, chemical carcinogens, and chemotherapeutic agents (22,23). Depending on the insult it can evoke cell cycle arrest (24)(25)(26)(27)(28), DNA repair (29), or apoptosis (30, 31) through sequence-specific and nonsequence-specific DNA binding and through both positive and negative mechanisms (32).…”
mentioning
confidence: 99%
“…Thus, p53 oscillates between latent and active sequencespecifi c DNA binding conformations and is differentially activated through posttranslational modifi cations including phosphorylation, acetylation and ubiquitination. On the other side, nonsequencespecifi c DNA binding may mediate other p53 actions [ 10 ]. In addition, p53 is also involved in mitochondrial-dependent cell death, collaborating in the execution of the apoptotic pathway.…”
Section: Introductionmentioning
confidence: 99%